Clostridial myonecrosis. A Case Report - Ledys Pérez Morales; Hidaleysi Quintana Hernández; Jorge E. Barletta del Castillo (Medisur)
Clostridium perfringens is an anaerobic Gram-positive bacillus with spore-forming ability. It is one of the most widely distributed bacterial pathogens in the environment. A case report of a female patient who had an accident with an agricultural implement, suffering proximal third tibial fracture with loss of the continuity of the bone in the right leg is presented. She underwent surgery and antibiotic therapy. Two days after being discharged, the patient came back complaining of acute pain and foul-smelling discharge in the surgical wound site. She was hospitalized with diagnostic impression of surgical wound sepsis caused by gas-producing germ. Gas gangrene was diagnosed, resulting in member amputation. Clostridium perfringens was isolated from the wound. Because of the importance of taking into account this possibility of infection in wounds caused by instruments potentially contaminated with environmental germs, it was decided to report this case.